Blood Malondialdehyde, Reproductive, and Lactation Performances of Ewes Fed High PUFA Rations Supplemented with Different Antioxidant Sources - Dilla Mareistia Fassah; Lilis Khotijah; Afton Atabany; Ridha Rianti Mahyardiani; Ridha Puspadini; Afi Yulian Putra (Faculty of Animal Science, Bogor Agricultural University, 2015)
The aims of this study were to evaluate the effect of vitamin E (vit E) and black tea extract (BTE) as antioxidant sources in high poly-unsaturated fatty acid (PUFA) rations on blood malondialdehyde (MDA) concentrations and the performance of reproduction and lactation of Garut ewes. Twelve ewes on late pregnancy periods were divided into completely randomized design (CRD) with 3 treatments and 4 replicates. The treatments were control: basal diet without antioxidant, vit E: basal diet supplemented with vit E, and BTE: basal diet supplemented with BTE. The results showed that vit E and BTE supplementation did not affect blood MDA concentration of ewes on late pregnancy, lactation periods, and weaning periods. Antioxidant sources supplementation had no effect on ewe’s nutrient intake, pre-lambing live weight change (LWC), and post-lambing average daily gain (ADG). Vit E supplementation had decreased the milk production, but both of antioxidant sources give positive effect on the milk composition. Nevertheless, the supplementation of vit E and BTE increased the twin type of birth. The vit E supplementation resulted higher lambing rate than BTE, although it had the highest mortality rate of twin lamb. BTE also had better lamb weaning weight than vit E. BTE and vit E gave similar results in ewes productivity on lactation period. In conclusion, this study confirmed that BTE was more effective used as antioxidant source than vit E to prevent the oxidative reaction of PUFA. Vit E supplementation on high PUFA ration reduced ewes milk production but it had similar reproduction performance with BTE.Key words: antioxidant, black tea extract, ewes, lactation, reproduction, vitamin E